The Development of Serial Assertive Comics about Reproduction Organs: Prevention Toward Early Child Sexual Abuse - Yulianti, Padmi Dhyah (Universitas Muhammadiyah Metro, 2019)
The prevalence of sexual abuse increases annually. The injuries have various impacts, both physical and psychological, for children. There is a need for effort to prevent and to prepare children to avoid sexual abuse. One of them is related to assertive comics with reproduction organs. This research uses the research and development approach done in two years. The first year was done in Central Semarang with subjects involving 28 teachers of preschool to fill the questionnaires, 30 teachers were asked to be in FGD process, and interview for 200 students to find out their initial understanding about sexual abuse, and testing the prototype in a limited trial run using 20 students of kindergarten. The technique of collecting data uses purposive sampling. Based on the findings from 200 students, 39 students have a great understanding of sexual abuse, 130 students with common knowledge, and 31 with deep understanding. Kindergarten students have the best experience in aspects of a safe location to play but have lower perceptions about parts of not to touch the body. Based on FGD results and questionnaires toward the teachers, it is gained result that teachers try to prevent sexual abuse, but from the side of media is still low and less variety. Based on the data, a prototype of assertive serial comics about reproduction organs are arranged as prevention toward early childhood sexual abuse. The suggestion, students with a lower understanding of sexual abuse, need active teachers' involvement in early childhood sexual abuse prevention programs using various media.